Bax translocation and mitochondrial fragmentation induced by Helicobacter pylori. Issue 6 (11th May 2004) - Ashktorab, H; Frank, S; Khaled, A R; Durum, S K; Kifle, B; Smoot, D T
Abstract : Background and aims: Previous in vitro and in vivo studies have revealed an association between Helicobacter pylori infection and apoptosis in gastric epithelial cells. Although involvement of the Bcl-2 family of proteins as well as cytochrome c release has been demonstrated in H pylori induced cell death, the exact role of the mitochondria during this type of programmed cell death has not been fully elucidated. Therefore, we sought to determine whether or not Bax translocation and mitochondrial fragmentation occur on exposure of gastric epithelial cells to H pylori, resulting in cell death. Methods: Experiments were performed with human gastric adenocarcinoma (AGS) cells, AGS cells transfected with the HPV-E6 gene (which inactivates p53 function), AGS-neo cells (transfected with the backbone construct), mouse embryonic fibroblasts (MEFs), and p19 ARF null (ARF −/− ) MEFs. Cells were incubated with a cag positive H pylori strain for up to 24 hours, lysed, and cytoplasmic and mitochondrial membrane fractions were analysed by western blot for Bax translocation. Results: Bax translocation was detected in AGS, AGS-neo, and normal MEF cells after exposure to H pylori for three hours, but not in ARF −/− MEFs cells. Translocation of Bax after H pylori incubation was also detected in AGS-E6 cells (inactive p53 gene) but to a lesser degree than in AGS-neo cells. In parallel studies, the mitochondrial morphology of living cells infected with H pylori was assessed by confocal microscopy. Mitochondrial fragmentation was detectable after 10 hours of H pylori incubation with AGS cells and after seven hours with MEF cells. In wild-type MEFs, mitochondrial fragmentation was significantly increased in comparison with ARF null MEFs (43% v 10.4%, respectively). Furthermore, mitochondrial depolarisation and caspase-3 activity were initiated within four hours in cells incubated with H pylori, and these events were inhibited by forced expression of Bcl-2. Conclusions: These data suggest that during H pylori induced apoptosis, Bax translocates to the mitochondria which subsequently undergo depolarisation and profound fragmentation. Functional ARF and p53 proteins may play an important role in H pylori induced mitochondrial modification.